Does Quality Influence Consumer Choice of Nursing Homes? Evidence from Nursing Home to Nursing Home Transfers - Richard A. Hirth; Jane C. Banaszak-Holl; Brant E. Fries; Marc N. Turenne (SAGE Publishing, 2003)
We estimated Cox proportional hazards models using assessment data from the Minimum Data Set to test whether nursing home residents and their proxies respond to quality of care by changing providers. Various indicators of poor quality increased the likelihood of transfer. Residents of for-profit homes or homes with excess capacity also were more likely to transfer. Inability to participate in care decisions and factors indicating frailty limited residents' ability to transfer. The apparent responsiveness to quality is encouraging. Nonetheless, because the absolute transfer rate is low, significant barriers to movement among nursing homes still may exist.